Tidak Ada Ruang untuk Bicara: Kajian Subalternitas dalam Naskah Monolog Balada Sumarah - Ikomah, Rinda Widya; Aliurridha, Aliurridha (Ruang Kata, 2025)
This article examines the representation of subalternity in the monologue script Balada Sumarah by Tentrem Lestari, focusing on the struggle of a woman named Sumarah who is marginalized due to the political and social stigma attached to her family, particularly after the G30S/PKI tragedy. The study aims to uncover how subaltern groups, in this case, Sumarah, attempt to speak out and seek justice within an oppressive system. A qualitative approach with text analysis is used to identify the dynamics of power, structural violence, and dominance relations reflected in the narrative. The research findings show that despite Sumarah's efforts to resist stigma through education, work, and attempts to speak in court, her voice and struggles remain ignored by the prevailing social system. Sumarah's death marks the final point, reflecting the inability of the social structure to provide space for subaltern groups to participate in the dominant discourse. The study also reveals how Balada Sumarah portrays symbolic violence and social exclusion as ongoing forms of oppression against marginalized groups